Comorbid ADHD/Depression Treated with Bupropion SR - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
A trial of bupropion sustained release (SR) was conducted in 24 adolescents (ages 11-16 years) with ADHD and either major depressive disorder or dysthymic disorder at the Department of Psychiatry, Dartmouth Medical School, Hanover, NH.